Changing the ties that bind: how incarceration impacts family relationships - Mowen, Thomas J. (Criminology & public policy, 2016)
By using a subsample of the Returning Home data set, we explored how family relationships change during reentry as a result of incarceration. Overall, we found that individuals who completed parenting classes, those with more frequent visits from family members, and Black and female respondents experienced positive changes in family relationships. On the other hand, single and divorced individuals, those with prior convictions and mental health issues, and individuals who reported barriers to family contact reported significant negative changes within the family relationship.